Advances in mergers and acquisitions. Vol. 15 - Finkelstein, Sydney; Cooper, Cary L. (Bingley, U.K. : Emerald, 2016)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspectives. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The papers published in this volume provide cutting edge ideas by leading scholars, and help to inform mergers and acquisitions research around the world.
The role of thriving and training in merger success: an integrative learning perspective / Mahima Thakur, Anjali Bansal, Peter Stokes -- On the role of the political regime in the choice between international acquisitions and joint ventures when entering an emerging market: evidence from russia / Olivier Bertrand, Marie-Ann Betschinger, Nina Bertschy, Roman Shidlauskas -- Cultural due diligence in mergers and acquisitions / Daniel Denison, Ia Ko -- Transitional governance trajectories: organization, place and space / Isabel Estrada, Florian Noseleit, Killian Mccarthy -- Are mergers and acquisitions socially responsible? evidence from the banking industry / Olimpia Meglio -- Interaction of cultural and technological distance in cross-border, high-technology acquisitions / Pankaj Patel, David King -- Peering into the executive mind: expanding our understanding of the motives for acquisitions / Adam Steinbach, Cynthia Devers, Gerry McNamara, Jingyu Li -- Related diversification: a critical reflection of relatedness and the diversification-performance linkage / Martin Weiss.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Strategic Planning; Business strategy; Consolidation and merger of corporations